CREATING VALUE AND GROWTH VIA FEMALE ENTREPRENEUR-LED SUSTAINABLE BRANDS: CONNECTING GLOBAL MARKET ENTRY, NETWORK BUILDING TECHNIQUES, AND PURPOSE-DRIVEN BUSINESS - Rovai, S.; Tavares, S. M.; Shroff, P. (EURAM- European Academy of Management 2025, 2025)
Purpose: The paper aims to investigate the female entrepreneur brand, examining how business with a purpose and in particular social sustainable actions are a critical component for new markets entry strategies internationally. Design/methodology/approach: An explorative qualitative empirical study focuses on case studies of women entrepreneurs in the sustainable fashion industry. Findings: Diverse international entry market strategies are identified associated to related strategies of business with a purpose that frame female entrepreneur brands with social or environmentally sustainable strategies in their international brand evolution. The study highlights the importance of the collective dimension of women’s engagement in social sustainability as well as supportive path for the preservation of the environment and heritage techniques when entering a new market as integrated values to the brand growth strategy. Research limitations/implications: Future research should expand the scope of case studies to include a wider range of sectors, geographical markets, and genders. Originality/value: Prior research on internationalisation as well as on business with a purpose has substantially neglected the female entrepreneur brand. This study frames and explores the female entrepreneur brand, offering insights into the role of social and environmental sustainability in the development of new entry market strategies with a purpose through business networks.